Factors affecting the presence of pumas in a highly conflictive area of Central Argentina - Guerisoli, Maria de Las Mercedes (2015)
Although Puma concolor is a widespread wild felid, little is known about its South American distribution and ecology, especially in areas with intense human activity. The puma was historically present throughout Argentina. In the second half of the last century, pumas were extirpated from most of Patagonia and have returned only in recent decades (Novaro and Walker 2005). In northeastern Argentina, high levels of habitat fragmentation caused a decline in puma populations (De Angelo et al. 2011). In the Buenos Aires province, with the advance of the agricultural and livestock frontiers, the range of the species has suffered a marked reduction (De Lucca 2010; Caruso et al. 2011). Illegal hunting is widespread.